2012
DOI: 10.1111/j.1365-2524.2011.01056.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of participatory research and photo-voice to support urban Aboriginal healthy eating

Abstract: The aim of this research was to work collaboratively with an urban Aboriginal community to understand meanings of food and food insecurity and strengthen responses to this issue. The project took place at the Wathaurong Aboriginal Cooperative in Geelong, South Eastern Australia in 2009-2010. Photo-voice research methods were used to explore meanings of food and food insecurity. This identified that food selections were influenced by family harmony, collectivism and satiation of hunger with cheap high carbohydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(78 citation statements)
references
References 25 publications
2
76
0
Order By: Relevance
“…In all three countries, for those Indigenous people operating under budget constraints, healthy foods from supermarkets were often unaffordable [60,61,64,65,68,71]. In the Australian context, Foley [68] found that despite the breadth of choices in the food system, the cost of healthy food remained a barrier for many urban Indigenous households.…”
Section: Affordability Of and Access To Store Foodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In all three countries, for those Indigenous people operating under budget constraints, healthy foods from supermarkets were often unaffordable [60,61,64,65,68,71]. In the Australian context, Foley [68] found that despite the breadth of choices in the food system, the cost of healthy food remained a barrier for many urban Indigenous households.…”
Section: Affordability Of and Access To Store Foodsmentioning
confidence: 99%
“…People were reluctant to experiment with new and different foods because they did not want to risk wasting food if it was going to be rejected by household members [69]. In particular, there was concern about the possibility of food wastage by children who rejected new foods [61].…”
Section: Affordability Of and Access To Store Foodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Karen Adams has worked in and with Aboriginal Community Controlled Health Organizations over a period of 20 years. This has involved working in community organizations with researchers and working as a researcher with community organizations, conducting research in areas such as social network analysis, child health, peer mentoring, health programme evaluation and analysis of surveillance systems (Adams & Spratling 2000Adams 2006;Adams & Walker 2006;Adams et al 2004aAdams et al , 2004bAdams et al , 2006aAdams et al , 2006bAdams et al , 2012Paasse & Adams 2011).…”
Section: Introductionmentioning
confidence: 99%